Blocking the quick attack in volleyball: a 3D kinematic analysis - Lobietti,R.; Fantozzi, S.; Merni, F. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The importance of the volleyball block against the quick attack is more important in the modern volleyball with new scoring system. Two types of tactics are used normally: the Read Block System (RBS) and the Commit Block System (CBS). A preliminary study was conducted to identify variables that quantified the differences between these two techniques. Four young players performing the RBS and the CBS were acquired by means of stereo-photogrammetry and kinematic variables were identified. The quantified analysis confirms coaches experience: in the RBS the hands arrive over the net in a shorter time, the feet start naturally wider but the jump performed has a lower height with respect to the CBS. Further longitudinal and transversal studies will be conducted with more subjects of different level and gender.